Solidarity with EU countries in crisis: Results of a 2015 Socio-Economic Panel (SOEP) survey - Holger Lengfeld; Martin Kroh (DIW Economic Bulletin, 2016)
In response to the European sovereign debt and currency crisis, the EU has begun to implement measures toward fiscal solidarity at least for the euro area. Survey data from the Socio-Economic Panel (SOEP) study show that just under half of all adults in Germany generally support providing assistance to EU countries experiencing financial difficulties. Almost one in three respondents also advocate the idea of an individual solidarity contribution for countries in crisis. In return, the majority of people in Germany expect these countries to reduce public spending and forge ahead with privatization. Only a minority call for the crisis country to make cuts in its social spending.
Keywords: N14; F15; F34; H81; Z13; 330; European Union; bail-out; fiscal solidarity; sovereign debt crisis; survey research